Integrated control technology of photovoltaic reactive power with source network coordination based on Multi-Agent Technology. Issue 4 (March 2021) - Li, Zhe; Tang, Chenghong; Liu, Cheng; Chen, Yonghua
Abstract: With the rapid development of photovoltaic power generation technology, its participation in reactive power control of distribution network technology has been widely concerned. However, photovoltaic output has great volatility and randomness, which also brings challenges to the security and stability of distribution network reactive power regulation. Firstly, considering the topology of photovoltaic power generation unit and the demand response of the grid point, the reactive power model of distribution network including photovoltaic power generation is established based on source grid coordinated regulation. Then, on the basis of the above research, a source-grid cooperative photovoltaic reactive power double-layer regulation model was established. These include the upper-level control model responding to grid reactive power control demand, and the lower-level control model uses particle swarm optimization algorithms to allocate and control the upper-level demand for each photovoltaic power generation unit. Finally, based on IEEE33 distribution network model, it is verified that the proposed method can effectively solve the impact of photovoltaic output fluctuation on reactive power regulation and control of distribution network.